Proses Pengambilan Keputusan Kepala Sekolah Dalam Meningkatkan Kinerja Guru Di SMP Terpadu Jamanis - Nisa Nurrohmah; Siti Julaeha (Garuda: Jurnal Pendidikan Kewarganegaraan Dan Filsafat, 2024)
Decisions mark the beginning of every action. In the context of educational organizations, decision making is directly related to the role of the school principal. As a manager, the principal has a key role in making decisions quickly, precisely and effectively, by utilizing data and information optimally to improve the performance of the educational environment. At Babakan Jamanis Integrated Middle School, the principal has succeeded in carrying out the decision-making process well. This can be seen from the stages carried out, including observation, data collection, planning and recording related to aspects of education in schools. The school principal also actively holds discussions with teachers to formulate policies, establish interpersonal relationships to manage events, provide ideas, involve teachers in training, and carry out supervision as part of management activities. All of these initiatives are reflected in teacher performance assessments which are not only useful for increasing teacher potential and performance, but also contribute to improving the quality of teaching and learning achievement at Babakan Jamanis Integrated Middle School.